Two different in vitro tests confirm the blocking activity of d-galactose lectins on the adhesion of Escherichia coli F4 to pig brush border receptors. Issue 1 (2nd January 2017) - Trevisi, Paolo; Miller, Bevis; Patel, Dilip; Bolognesi, Andrea; Bortolotti, Massimo; Bosi, Paolo
Abstract: The pathogenicity of Enterotoxigenic Escherichia coli (ETEC) expressing F4ac (K88) fimbrial adhesin and its adhesion to the pig jejunum surface is genetically controlled by the presence of a specific receptor glycoprotein on brush borders of the epithelium. We firstly screened the degree of inhibition obtained with ten galactose-recognising lectins – respectively from Abrus precatorius (APA-I); Coregonus maraena ; Euphorbia characias ; Crotalaria juncea ; Sambucus ebulus (SEL1d); Sambucus nigra (SNAV); Coregonus peled ; Momordica charantia (MCL); Trychosanthes kirilowii ; Adenia racemosa –, by an ELISA test based on intestinal brush border sensitive for E. coli F4ac adhesion and ETEC F4ac fimbrial antigen. Three lectins significantly inhibited the fimbrial adhesion and the highest value was obtained by Crotalaria juncea lectin ( p < .01). The results were then confirmed by an in vitro inhibition test of ETEC adhesion to villi isolated from ETEC susceptible pigs. The favourable results obtained with the supplementation of twod -galactose lectins against the ETEC adhesion to intestinal villi stimulate in vivo testing of the addition of these lectins in the piglet feeding